1991
DOI: 10.1128/jb.173.23.7540-7548.1991
|View full text |Cite
|
Sign up to set email alerts
|

Potential DNA slippage structures acquired during evolutionary divergence of Acinetobacter calcoaceticus chromosomal benABC and Pseudomonas putida TOL pWW0 plasmid xylXYZ, genes encoding benzoate dioxygenases

Abstract: The xylXYZ DNA region is carried on the TOL pWW0 plasmid in Pseudomonas putida and encodes a benzoate dioxygenase with broad substrate specificity. The DNA sequence of the region is presented and compared with benABC, the chromosomal region encoding the benzoate dioxygenase of Acinetobacter calcoaceticus. Corresponding genes from the two biological sources share common ancestry: comparison of aligned XylX-BenA, XylY-BenB, and XylZ-BenC amino acid sequences revealed respective identities of 58.3, 61.3, and 53%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 40 publications
0
70
0
Order By: Relevance
“…BenABC of Acinetobacter sp. ADP1, on the other hand, exhibits narrow substrate specificity, showing little or no oxidation of most substituted benzoates (Neidle et al, 1991). The 3CB degrader Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…BenABC of Acinetobacter sp. ADP1, on the other hand, exhibits narrow substrate specificity, showing little or no oxidation of most substituted benzoates (Neidle et al, 1991). The 3CB degrader Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“….... (Taylor, 1988 (Gowri & Campbell, 1989) DMPP-PSEPU = Hydroxylase P5 protein (EC 1.14.13.7) phenol 2-monooxygenase P5 component-Pseudomonas (Nordlund et al, 1990) S15303 = Hypothetical protein 7.6-Salmonella typhimurium (Jiang et al, 1991) MEMC-METCA = Methane monooxygenase component C (EC 1.14.13.25) methane hydroxylase -Methylococcus capsula (Stainthorpe et al, 1990) XYLZ-PSEPU = E 1.2-dioxygenase electron transfer component contains ferredoxin and ferredoxin-NAD(+) (Harayama et al, 1991 (Karplus et al, 1991) amino-terminus was revealed, comprising G[QK] [HFYS] (close to strand S1-5 in Fig. 3).…”
Section: Sequence Alignmentmentioning
confidence: 99%
“…The purified protein had a molecular mass of 42 kDA by the gel filtration analysis, indicating that the reductase is monomeric. The NADH :acceptor reductase component of xylene monooxygenase is a member of the protein family comprising the electron-transfer components of benzoate 1,2-dioxygenase from Pseudomonas arvilla [26,271, and from Acinetobacter calcoaceticus [28], toluate 1,2-dioxygenase from P. putida (pWW0) [29], phenol hydroxylase from Pseudomonas sp. CF600 [30,311, and soluble methane monooxygenase from Methylcoccus capsufutus (Bath) [15, 32, 331.…”
Section: General Characteristics Of the Nadh: Acceptor Reductasementioning
confidence: 99%